Trade Transformation In The Digital Era: Agency Role, Opportunities And Challenges - Yufriadi, Ferdi; Syahriani, Fadilla; Afifi, Abdullah A (IDRIS Darulfunun Institute, 2024)
The evolution of trade dynamics in the digital age has brought forth a landscape filled with both opportunities and challenges. This study delves into the realm of trade transformation within the context of the digital era, employing the theoretical framework presented by Anthony Giddens. Giddens' concepts surrounding modernity, the structure of society, and the role of agents in shaping modern-day interactions serve as the lens through which this analysis navigates the multifaceted landscape of contemporary trade. This study investigates how digital advancements have reshaped trade mechanisms, revealing a landscape marked by significant opportunities for growth alongside challenges stemming from rapid technological change. Through the description of the opportunities presented by digital technologies, as well as the obstacles they introduce, the study provides insights into the dual nature of trade evolution in the digital era. It emphasizes the need for a nuanced understanding of how digital tools and platforms are integrated into trade activities, and how these integrations affect both the opportunities available for economic expansion and the challenges of adapting to a swiftly transforming commerce ecosystem. By examining the interplay between digital advancements and trade mechanisms, this research sheds light on the intricate balance between opportunities for growth and the challenges posed by rapid technological evolution, offering insights crucial for navigating the complexities of today's global trade environment.